Polydomus karssenii gen. nov. sp. nov. is a dark septate endophyte with a bifunctional lifestyle parasitising eggs of plant parasitic cyst nematodes (Heterodera spp.) - Samad Ashrafi; Jan-Peer Wennrich; Yvonne Becker; Jose G. Maciá-Vicente; Anke Brißke-Rode; Matthias Daub; Torsten Thünen; Abdelfattah A. Dababat; Maria R. Finckh; Marc Stadler; Wolfgang Maier (IMA Fungus)
Abstract In this study fungal strains were investigated, which had been isolated from eggs of the cereal cyst nematode Heterodera filipjevi, and roots of Microthlaspi perfoliatum (Brassicaceae). The morphology, the interaction with nematodes and plants and the phylogenetic relationships of these strains originating from a broad geographic range covering Western Europe to Asia Minor were studied. Phylogenetic analyses using five genomic loci including ITSrDNA, LSUrDNA, SSUrDNA, rpb2 and tef1-α were carried out. The strains were found to represent a distinct phylogenetic lineage most closely related to Equiseticola and Ophiosphaerella, and Polydomus karssenii (Phaeosphaeriaceae, Pleosporales) is introduced here as a new species representing a monotypic genus. The pathogenicity tests against nematode eggs fulfilled Koch’s postulates using in vitro nematode bioassays and showed that the fungus could parasitise its original nematode host H. filipjevi as well as the sugar beet cyst nematode H. schachtii, and colonise cysts and eggs of its hosts by forming highly melanised moniliform hyphae. Light microscopic observations on fungus-root interactions in an axenic system revealed the capacity of the same fungal strain to colonise the roots of wheat and produce melanised hyphae and microsclerotia-like structure typical for dark septate endophytes. Confocal laser scanning microscopy further demonstrated that the fungus colonised the root cells by predominant intercellular growth of hyphae, and frequent formation of appressorium-like as well as penetration peg-like structures through internal cell walls surrounded by callosic papilla-like structures. Different strains of the new fungus produced a nearly identical set of secondary metabolites with various biological activities including nematicidal effects irrespective of their origin from plants or nematodes.